PERLINDUNGAN TERHADAP TENAGA KERJA DI INDONESIA DARI PERSPEKTIF KONVENSI ILO (INTERNATIONAL LABOUR ORGANIZATION) NOMOR 105 DAN NOMOR 182 - Maria Seraphine Kartika Dewi; Putu Tuni Cakabawa Landra; I Gede Pasek Eka Wisanjaya (Kertha Negara : Journal Ilmu Hukum, 2015)
A number of cases indicate abuse that received by workers at their workplace inIndonesia. It is certainly ironic because Indonesia has ratified the ILO Conventionnumber 105 and ILO Convention number 182 that provide protection both legally andpsychologically. Legal protection for labor actually invovles national regulationsbecause these conventions oblige the States to take immediate effective action onprotection and prohibition. This paper is a normative legal research that addresses theissue of legal protection for workers in Indonesia from the perspective of theconventions in concern and any kind obstacles for its implementation.